(untitled) - Rosai, Juan; Juan Rosai (Edinburgh, 2011)
Rosai and Ackerman’s Surgical Pathology delivers the authoritative guidance you need to overcome virtually any challenge in surgical pathology. Recognized globally for his unmatched expertise, preeminent specialist Juan Rosai, MD brings you state-of-the-art coverage of the latest advancements in immunohistochemistry, genetics, molecular biology, prognostic/predictive markers, and much more - equipping you to effectively and efficiently diagnose the complete range of neoplastic and non-neoplastic entities
Includes bibliographical references and index
Keywords: Pathology; Surgical